The Concept of Eschatology in the Late Thought of Martin Heidegger - Mateo Belgrano (Filozofia)
The aim of this study is to analyze the Christian heritage in the late philosophy of the German philosopher Martin Heidegger. My hypothesis is that behind the concept of the “history of being” (Seinsgeschichte) there is an influence of the concepts of Christian eschatology and parousia that Heidegger dealt with in his early days as a professor in Freiburg. Although the philosopher had long since broken his relationship with Catholicism, these notions return in a secularized form years later in his thinking on the history of being.